2014
DOI: 10.3109/10641955.2014.920026
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of parental KIR and fetal HLA-C genotypes with the risk of preeclampsia

Abstract: Women with KIR AA genotype and fewer C2 genes than their fetuses were at risk for preeclampsia in the Chinese Han population, supporting that maternal-fetal KIR-HLA-C interaction plays an important role in preeclampsia development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Furthermore, this finding shows consistency with earlier research works in other populations [66,67]. It is believed that activating KIR2DS1 refers to a protective determinant, and insufficient activation of uNK cells is expected to lead to decreased invasion of trophoblasts, thereby resulting in PE [70]. Moreover, it was also indicated that if the fetus possessed more numbers of HLA-C2 genes as compared with the mother, the maternal KIR AA genotype was correlated with a higher risk for PE [70].…”
Section: The Roles Of Kir and Hla-c In Immunity Normal Pregnancy Ansupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, this finding shows consistency with earlier research works in other populations [66,67]. It is believed that activating KIR2DS1 refers to a protective determinant, and insufficient activation of uNK cells is expected to lead to decreased invasion of trophoblasts, thereby resulting in PE [70]. Moreover, it was also indicated that if the fetus possessed more numbers of HLA-C2 genes as compared with the mother, the maternal KIR AA genotype was correlated with a higher risk for PE [70].…”
Section: The Roles Of Kir and Hla-c In Immunity Normal Pregnancy Ansupporting
confidence: 90%
“…In the context of China, women having PE have an evidently larger frequency of KIR AA genotype, primarily containing the inhibitory receptors, in addition to the lower frequency of maternal activating gene KIR2DS1 as compared with normal pregnancies [70]. Furthermore, this finding shows consistency with earlier research works in other populations [66,67].…”
Section: The Roles Of Kir and Hla-c In Immunity Normal Pregnancy Ansupporting
confidence: 88%
See 1 more Smart Citation
“…The authors found that the mothers lacking activating KIRs were more at risk of preeclampsia (27). Yu et al found that in Han Chinese, mothers with KIR A haplotype (AA genotype) (the haplotype consisting inhibitory KIRs) were more at risk of preeclampsia (28). Another study on Han Chinese showed that lack of activating KIRs is associated with preeclampsia (29), a condition occurring in AA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of two maternal KIR A haplotypes (KIR AA) and fetal HLA-C2 has been demonstrated more common in preeclampsia by comparing 200 cases of preeclampsia patients with 201 cases with a normal pregnancy in British women (38). The preeclampsia patients from China also show a higher frequency of KIR AA (93,94). For Mexico preeclampsia patients, KIR AA is even predominated (95).…”
Section: Dnk Cells and Pathological Pregnancy Preeclampsiamentioning
confidence: 99%